An environmentally friendly flame-retardant rubber-plastic composite shed blanket

By adopting the rubber-plastic composite structure of polytetrafluoroethylene anti-aging layer, intermediate insulation layer and fire-resistant silicon fiber veneer in the insulation shed, the problems of poor aging resistance and flame retardancy of the existing insulation shed are solved, and the problem of poor aging resistance and flame retardancy of the existing insulation shed is realized. Better insulation performance, service life and environmental protection.

CN114434923BActive Publication Date: 2025-02-18HEBEI SHENZHOU THERMAL INSULATION BUILDING MATERIAL GRP CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202210234226.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-03-10
Publication Date
2025-02-18
Estimated Expiration
2042-03-10

AI Technical Summary

Technical Problem

The existing insulation sheds have poor aging resistance and flame retardancy during use, resulting in degradation of insulation performance and flammable, and toxic gases will be generated during combustion, which is not environmentally friendly.

Method used

Using a rubber-plastic composite structure of polytetrafluoroethylene anti-aging layer, intermediate insulation layer and fire-resistant silicon fiber veneer layer arranged from top to bottom, the polytetrafluoroethylene anti-aging layer is passed through anionic fluorocarbon surfactant and tri-isometric Stearoyl isopropyl titanate and porous calcium carbonate are mixed and melt-extruded. The intermediate insulation layer contains flame retardant and protective wax. The fire-resistant silicon fiber veneer is a glass fiber cloth layer coated with fluorosilicone rubber.

Benefits of technology

It significantly improves the aging resistance, flame retardancy and breathability of rubber and plastic composite sheds, extends the service life, ensures waterproof and thermal insulation performance in rainy and cold weather, and does not produce toxic gases, which is environmentally friendly and reliable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of shed blankets, and provides an environmentally friendly flame-retardant rubber-plastic composite shed blanket. The composite shed blanket comprises a polytetrafluoroethylene anti-aging layer, an intermediate thermal insulation layer and a fireproof silicone fiber veneer layer arranged in sequence from top to bottom; the polytetrafluoroethylene anti-aging layer comprises the following components in parts by weight: 60-100 parts of polytetrafluoroethylene, 4-7 parts of fluorocarbon surfactant, 1-1.5 parts of triisostearoyl titanate isopropyl, and 13-18 parts of porous calcium carbonate; the intermediate thermal insulation layer comprises the following components in parts by weight: The components in parts by weight are: 15-20 parts of nitrile rubber, 3-5 parts of polyvinyl chloride resin, 3-5 parts of ethylene-vinyl acetate copolymer, 20-30 parts of talc, 13-15 parts of chlorinated paraffin oil, 1-2 parts of epoxy soybean oil, 2-4 parts of protective wax, 3-5 parts of carbon black, 0.2-0.3 parts of active agent, 0.1-0.3 parts of stearic acid, 10-20 parts of flame retardant, 0.1-0.3 parts of antioxidant, 1-3 parts of accelerator, and 0.1-0.3 parts of vulcanizing agent. Through the above technical solution, the problem of poor aging resistance and flame retardancy of the insulation shed in the related art is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of shed blankets, and in particular to an environmentally friendly flame-retardant rubber-plastic composite shed blanket. Background Art

[0002] An ideal greenhouse blanket should have the characteristics of heat preservation, waterproof and moisture-proof, light transmittance, easy to fold and unfold, and long service life. With the rapid development of greenhouse planting industry, greenhouse blankets are gradually being accepted by farmers. As the "cotton coat" of the greenhouse, the greenhouse blanket covers the surface of the greenhouse, which increases the greenhouse temperature and improves the greenhouse's ability to resist wind, rain and snow.

[0003] Insulating shed blankets are mostly made of straw felt and multi-layer non-woven cotton felt, and have the following problems: the thermal insulation performance of the insulating shed blankets decreases after being used for a period of time. This is because in the outdoor environment, rain, snow, condensation and frost at night cause water to slowly seep into the shed blankets, making the quilts damp, thereby greatly reducing the thermal insulation performance of the shed blankets; secondly, insulating shed blankets are flammable and produce toxic gases when burned, which is not environmentally friendly.

[0004] In order to solve the above problems, an invention patent application with application number 201310632648.6 discloses a foam thermal insulation quilt, including a quilt body, which comprises an outer waterproof layer, an outer thermal insulation layer, an inner thermal insulation layer, and an inner fireproof layer from the outside to the inside, and has good thermal insulation, waterproof and fireproof effects. However, since the outer waterproof layer is made of waterproof rubber cloth, the waterproof rubber cloth has poor weather resistance and flame retardancy, resulting in the aging, cracking and decomposition of the waterproof rubber cloth when the thermal insulation quilt is used for a long time in hot or cold weather in the outdoor environment, thereby affecting the service life of the thermal insulation quilt. At the same time, the flame retardant performance of the waterproof rubber cloth is poor. Although the inner layer of the thermal insulation quilt has a fireproof layer, the outer layer is not fireproof, which will also affect the use of the thermal insulation quilt. Summary of the invention

[0005] The invention provides an environmentally friendly flame-retardant rubber-plastic composite shed quilt, which solves the problem of poor aging resistance and flame retardancy of the thermal insulation shed quilt in the prior art.

[0006] The technical solution of the present invention is as follows:

[0007] An environmentally friendly flame-retardant rubber-plastic composite shed blanket comprises a polytetrafluoroethylene anti-aging layer, an intermediate thermal insulation layer and a fireproof silicon fiber veneer layer arranged in sequence from top to bottom.

[0008] The polytetrafluoroethylene anti-aging layer comprises the following components in parts by weight: 60-100 parts of polytetrafluoroethylene, 4-7 parts of anionic fluorocarbon surfactant, 1-1.5 parts of triisostearyl isopropyl titanate, and 13-18 parts of porous calcium carbonate.

[0009] As a further technical solution, the intermediate insulation layer includes the following components in parts by weight: 15-20 parts of nitrile rubber, 3-5 parts of polyvinyl chloride resin, 4-7 parts of foaming agent, 3-5 parts of ethylene-vinyl acetate copolymer, 20-30 parts of talc, 13-15 parts of chlorinated paraffin oil, 1-2 parts of epoxy soybean oil, 2-4 parts of protective wax, 3-5 parts of carbon black, 0.2-0.3 parts of active agent, 0.1-0.3 parts of stearic acid, 10-20 parts of flame retardant, 0.1-0.3 parts of antioxidant, 1-3 parts of accelerator, and 0.1-0.3 parts of vulcanizing agent.

[0010] As a further technical solution, the fireproof silicone fiber veneer layer is a glass fiber cloth layer coated with fluorosilicone rubber, and the mass ratio of the fluorosilicone rubber to the glass fiber cloth is (10-15): (85-90).

[0011] As a further technical solution, the thickness of the polytetrafluoroethylene anti-aging layer is 0.2 mm, the thickness of the middle layer is 1-5 cm, and the thickness of the fireproof silicone fiber veneer layer is 0.2 mm.

[0012] As a further technical solution, the particle size of the porous calcium carbonate is 200-300nm.

[0013] As a further technical solution, the preparation method of porous calcium carbonate includes the following steps: dissolving calcium chloride in a poloxamer aqueous solution, adding sodium carbonate, reacting at 60-70° C. for 8-10 hours after dissolution, and centrifuging the obtained product to wash and dry to obtain porous calcium carbonate.

[0014] As a further technical solution, the molar ratio of the calcium chloride to the sodium carbonate is 1:1.

[0015] As a further technical solution, the preparation method of the polytetrafluoroethylene anti-aging layer includes the following steps: polytetrafluoroethylene is mixed with anionic fluorocarbon surfactant, triisostearyl isopropyl titanate, and porous calcium carbonate, and then melt-extruded to obtain the polytetrafluoroethylene anti-aging layer.

[0016] As a further technical solution, the polytetrafluoroethylene anti-aging layer, the middle thermal insulation layer and the fireproof silicone fiber veneer layer are composited by hot pressing to obtain an environmentally friendly rubber-plastic composite shed blanket.

[0017] The working principle and beneficial effects of the present invention are:

[0018] 1. In the present invention, a polytetrafluoroethylene anti-aging layer is arranged on the middle thermal insulation layer. The polytetrafluoroethylene anti-aging layer is based on polytetrafluoroethylene and is melt-extruded after being mixed with anionic fluorocarbon surfactant, triisostearyl isopropyl titanate and porous calcium carbonate. The polytetrafluoroethylene and calcium carbonate are compatible with each other, which significantly improves the weather resistance of the polytetrafluoroethylene anti-aging layer. The polytetrafluoroethylene and the anionic fluorocarbon surfactant act synergistically, which significantly improves the flame retardancy of the polytetrafluoroethylene anti-aging layer. Therefore, the rubber-plastic composite shed with the polytetrafluoroethylene anti-aging layer as the upper layer has good aging resistance and flame retardancy, which effectively solves the problem of poor aging resistance and flame retardancy of the thermal insulation shed in the prior art.

[0019] 2. In the present invention, the upper polytetrafluoroethylene anti-aging layer has good flame retardancy, and the lower fireproof silicone fiber veneer layer also has good fire resistance, so that the rubber-plastic composite shed has good flame retardancy both inside and outside during actual use, and is more practical.

[0020] 3. In the present invention, porous calcium carbonate is added to the polytetrafluoroethylene anti-aging layer, which significantly improves the air permeability of the polytetrafluoroethylene anti-aging layer, and the middle insulation layer and the fireproof silicone fiber veneer layer also have good air permeability, so that the rubber-plastic composite shed has good air permeability and better performance.

[0021] 4. In the present invention, the anti-aging layer formed by melt extrusion after mixing with polytetrafluoroethylene as a matrix, anionic fluorocarbon surfactant, triisostearyl titanate isopropyl, and porous calcium carbonate also has good waterproof properties. After hot-pressing and compounding with the intermediate thermal insulation layer, a 0.2 mm thick waterproof and breathable film is formed on the intermediate thermal insulation layer. The good waterproof property enables the rubber-plastic composite shed to effectively prevent the penetration of water droplets when used in rainy weather, thereby effectively avoiding the problem of deterioration of thermal insulation performance of the rubber-plastic composite shed due to the penetration of water droplets during use.

[0022] 5. In the present invention, the particle size of porous calcium carbonate is 200-300nm. When added alone to a polytetrafluoroethylene matrix, porous calcium carbonate is prone to aggregation and uneven dispersion in the polytetrafluoroethylene matrix. The addition of anionic fluorocarbon surfactant and triisostearyl isopropyl titanate, the synergistic compatibility of the two makes the porous calcium carbonate evenly dispersed in the polytetrafluoroethylene matrix, thereby further improving the air permeability of the polytetrafluoroethylene anti-aging layer. DETAILED DESCRIPTION

[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] In the following embodiment, the preparation method of porous calcium carbonate is as follows: 11.1g calcium chloride is dissolved in 200mL poloxamer aqueous solution, 10.6g sodium carbonate is added, and the mixture is reacted at 65°C for 9h after dissolution, and the obtained product is centrifuged, washed and dried to obtain porous calcium carbonate with a particle size of 200-300nm; the mass concentration of the poloxamer aqueous solution is 5%, and the model of poloxamer is F127; the foaming agent is foaming agent DAB, the activating agent is zinc oxide, the accelerator is N-cyclohexyl-2-benzothiazole sulfenamide, the vulcanizing agent is sulfur, and the antioxidant is antioxidant D;

[0025] Example 1

[0026] An environmentally friendly flame-retardant rubber-plastic composite shed blanket, comprising a polytetrafluoroethylene anti-aging layer, an intermediate thermal insulation layer and a fireproof silicone fiber veneer layer arranged in sequence from top to bottom, the thickness of the polytetrafluoroethylene anti-aging layer is 0.2 mm, the thickness of the intermediate layer is 1-5 cm, and the thickness of the fireproof silicone fiber veneer layer is 0.2 mm;

[0027] The polytetrafluoroethylene anti-aging layer comprises the following components in parts by weight: 60 parts of polytetrafluoroethylene, 4 parts of sulfonic acid anionic fluorocarbon surfactant, 1 part of triisostearoyl isopropyl titanate, and 13 parts of porous calcium carbonate;

[0028] The middle insulation layer includes the following components in parts by weight: 15 parts of nitrile rubber, 3 parts of polyvinyl chloride resin, 4 parts of foaming agent, 3 parts of ethylene-vinyl acetate copolymer, 20 parts of talc, 13 parts of chlorinated paraffin oil, 1 part of epoxy soybean oil, 2 parts of protective wax, 3 parts of carbon black, 0.2 parts of active agent, 0.1 parts of stearic acid, 10 parts of flame retardant, 0.1 parts of antioxidant, 1 part of accelerator, and 0.1 parts of vulcanizing agent;

[0029] The fireproof silicone fiber veneer layer is a glass fiber cloth layer coated with fluorosilicone rubber, and the mass ratio of fluorosilicone rubber to glass fiber cloth is 10: (85-90);

[0030] The method for preparing the above-mentioned environmentally friendly flame-retardant rubber-plastic composite shed blanket comprises the following steps:

[0031] (1) Mixing polytetrafluoroethylene with a sulfonic acid anionic fluorocarbon surfactant, triisostearyl isopropyl titanate, and porous calcium carbonate, and then melt-extrude the mixture to obtain a polytetrafluoroethylene anti-aging layer;

[0032] (2) Putting nitrile rubber, polyvinyl chloride resin, foaming agent, flame retardant, talc, carbon black, chlorinated paraffin oil, epoxy soybean oil, ethylene-vinyl acetate copolymer, antioxidant, protective wax, activator and stearic acid into an internal mixer for blending, and when the blending temperature reaches 165°C, discharging the material to an open mixer for cooling and re-blending, the temperature drops to 80°C, and the sheet is allowed to cool naturally and then stored for 24 hours, and then the sheet is further mixed in the open mixer, and a vulcanizing agent and an accelerator are added, and the mixed material is uniformly formed into strips; the strips are extruded into shape by an extruder, and then sent to an oven for vulcanization and foaming to obtain an intermediate insulation layer;

[0033] (3) Coating fluorosilicone rubber on the surface of the glass fiber cloth to obtain a fire-resistant silicone fiber veneer layer;

[0034] (4) The polytetrafluoroethylene anti-aging layer is hot-pressed with the middle thermal insulation layer and the fireproof silicone fiber veneer layer to obtain an environmentally friendly flame-retardant rubber-plastic composite shed blanket.

[0035] Example 2

[0036] An environmentally friendly flame-retardant rubber-plastic composite shed blanket, comprising a polytetrafluoroethylene anti-aging layer, an intermediate thermal insulation layer and a fireproof silicone fiber veneer layer arranged in sequence from top to bottom, the thickness of the polytetrafluoroethylene anti-aging layer is 0.2 mm, the thickness of the intermediate layer is 1-5 cm, and the thickness of the fireproof silicone fiber veneer layer is 0.2 mm;

[0037] The polytetrafluoroethylene anti-aging layer comprises the following components in parts by weight: 80 parts of polytetrafluoroethylene, 5 parts of phosphate-based anionic fluorocarbon surfactant, 1.2 parts of triisostearoyl isopropyl titanate, and 15 parts of porous calcium carbonate;

[0038] The middle insulation layer includes the following components in parts by weight: 18 parts of nitrile rubber, 4 parts of polyvinyl chloride resin, 5 parts of foaming agent, 4 parts of ethylene-vinyl acetate copolymer, 25 parts of talc, 14 parts of chlorinated paraffin oil, 1.5 parts of epoxy soybean oil, 3 parts of protective wax, 4 parts of carbon black, 0.25 parts of active agent, 0.2 parts of stearic acid, 15 parts of flame retardant, 0.2 parts of antioxidant, 2 parts of accelerator, and 0.2 parts of vulcanizing agent;

[0039] The fireproof silicone fiber veneer layer is a glass fiber cloth layer coated with fluorosilicone rubber, and the mass ratio of fluorosilicone rubber to glass fiber cloth is (10-15): (85-90);

[0040] The preparation method of the above-mentioned environmentally friendly flame-retardant rubber-plastic composite shed blanket is the same as that of Example 1.

[0041] Example 3

[0042] An environmentally friendly flame-retardant rubber-plastic composite shed blanket, comprising a polytetrafluoroethylene anti-aging layer, an intermediate thermal insulation layer and a fireproof silicone fiber veneer layer arranged in sequence from top to bottom, the thickness of the polytetrafluoroethylene anti-aging layer is 0.2 mm, the thickness of the intermediate layer is 1-5 cm, and the thickness of the fireproof silicone fiber veneer layer is 0.2 mm;

[0043] The polytetrafluoroethylene anti-aging layer comprises the following components in parts by weight: 100 parts of polytetrafluoroethylene, 7 parts of carboxylic anionic fluorocarbon surfactant, 1.5 parts of triisostearoyl isopropyl titanate, and 18 parts of porous calcium carbonate;

[0044] The middle insulation layer includes the following components in parts by weight: 20 parts of nitrile rubber, 5 parts of polyvinyl chloride resin, 7 parts of foaming agent, 5 parts of ethylene-vinyl acetate copolymer, 30 parts of talc, 15 parts of chlorinated paraffin oil, 2 parts of epoxy soybean oil, 4 parts of protective wax, 5 parts of carbon black, 0.3 parts of active agent, 0.3 parts of stearic acid, 20 parts of flame retardant, 0.3 parts of antioxidant, 3 parts of accelerator, and 0.3 parts of vulcanizing agent;

[0045] The fireproof silicone fiber veneer layer is a glass fiber cloth layer coated with fluorosilicone rubber, and the mass ratio of fluorosilicone rubber to glass fiber cloth is (10-15): (85-90);

[0046] The preparation method of the above-mentioned environmentally friendly flame-retardant rubber-plastic composite shed blanket is the same as that of Example 1.

[0047] Comparative Example 1

[0048] A polytetrafluoroethylene anti-aging layer, which differs from Example 1 only in that porous calcium carbonate is not added.

[0049] Comparative Example 2

[0050] A polytetrafluoroethylene anti-aging layer, which is different from Example 1 only in that no sulfonic acid anionic fluorocarbon surfactant is added.

[0051] Comparative Example 3

[0052] A polytetrafluoroethylene anti-aging layer, which is different from Example 1 only in that triisostearoyl isopropyl titanate is not added.

[0053] Comparative Example 4

[0054] A polytetrafluoroethylene anti-aging layer, which is different from Example 1 only in that the sulfonic acid anionic fluorocarbon surfactant and triisostearoyl titanate isopropyl are not added.

[0055] The flame retardancy test of the polytetrafluoroethylene anti-aging layer obtained in Example 1 and Comparative Examples 1-4 was carried out in accordance with the provisions of GB / T2406-1993 "Plastic Combustion Performance Test Method Oxygen Index Method". The test results are shown in the following table:

[0056] Table 1 Flame retardancy test results of polytetrafluoroethylene anti-aging layers obtained in Example 1 and Comparative Examples 1-4

[0057]

[0058] It can be seen from the data in the above table that the oxygen index of the polytetrafluoroethylene anti-aging layer obtained in Example 1 is 28.6, which has a good flame retardant effect. By comparing Example 1 with Comparative Examples 1 and 2, it can be seen that the addition of fluorosilicone surfactant significantly improves the oxygen index of the polytetrafluoroethylene anti-aging layer, and the addition of porous calcium carbonate further improves the oxygen index of the polytetrafluoroethylene anti-aging layer.

[0059] The polytetrafluoroethylene anti-aging layer obtained in Example 1 and Comparative Examples 1-4 was subjected to an anti-aging test. The test method was carried out in accordance with the provisions of GB / T 7141-2008 "Plastic Thermal Aging Test Method". Test samples were placed in a thermal aging test chamber, and the failure cycle of the samples was tested at 50°C. The test results are shown in the following table:

[0060] Table 2 Anti-aging test results of polytetrafluoroethylene anti-aging layers obtained in Example 1 and Comparative Examples 1-4

[0061]

[0062] It can be seen from the data in the above table that the polytetrafluoroethylene anti-aging layer obtained in Example 1 has good anti-aging properties. By comparing Example 1 with Comparative Examples 1-4, it can be seen that the addition of porous calcium carbonate significantly improves the anti-aging properties of the polytetrafluoroethylene anti-aging layer, and the anionic fluorocarbon surfactant and triisostearyl isopropyl titanate synergistically further improve the anti-aging properties of the polytetrafluoroethylene anti-aging layer.

[0063] The polytetrafluoroethylene anti-aging layer obtained in Examples 1-3 was tested for water resistance. The test method was in accordance with GB / T1037-1988 "Test method for water vapor permeability of plastic films and sheets (cup method)" Test conditions: T = (38 ± 0.6) ° C, RH = (90 ± 2)%, and the test results are shown in the following table:

[0064] Table 3 Waterproof test results of the polytetrafluoroethylene anti-aging layer obtained in Examples 1-3:

[0065]

[0066] It can be seen from the data in the above table that the polytetrafluoroethylene anti-aging layer prepared in Examples 1-3 has a small water vapor permeability in the water vapor permeability test, indicating that the polytetrafluoroethylene anti-aging layer of the present invention has good waterproof properties, so that the rubber-plastic composite shed with the polytetrafluoroethylene anti-aging layer as the upper layer can effectively prevent the penetration of water droplets when used in rainy weather, thereby effectively avoiding the problem of deterioration of thermal insulation performance of the rubber-plastic composite shed due to water droplets infiltration during use.

[0067] The air permeability test of the polytetrafluoroethylene anti-aging layer obtained in Example 1 and Comparative Examples 1-4 was carried out using an air permeability tester, the test gas was nitrogen, the test time was 24 hours, the test pressure was 0.2 MPa, and the test results are shown in the following table:

[0068] Table 4 Air permeability test results of polytetrafluoroethylene anti-aging layer of Example 1 and Comparative Examples 1-4

[0069]

[0070] It can be seen from the data in the above table that the polytetrafluoroethylene anti-aging layer of Example 1 has good air permeability. By comparing Example 1 with Comparative Examples 1-4, it can be seen that the addition of porous calcium carbonate significantly improves the air permeability of the polytetrafluoroethylene anti-aging layer, and the anionic fluorocarbon surfactant and triisostearyl isopropyl titanate synergistically further improve the air permeability of the polytetrafluoroethylene anti-aging layer.

[0071] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. An environmentally friendly flame-retardant rubber-plastic composite shed blanket, characterized in that: The composite shed includes a polytetrafluoroethylene anti-aging layer, an intermediate insulation layer and a fireproof silicon fiber veneer layer arranged in sequence from top to bottom. The polytetrafluoroethylene anti-aging layer comprises the following components in parts by weight: 60-100 parts of polytetrafluoroethylene, 4-7 parts of anionic fluorocarbon surfactant, 1-1.5 parts of triisostearoyl isopropyl titanate, and 13-18 parts of porous calcium carbonate; The particle size of the porous calcium carbonate is 200-300 nm; The preparation method of the porous calcium carbonate comprises the following steps: dissolving calcium chloride in a poloxamer aqueous solution, adding sodium carbonate, reacting at 60-70° C. for 8-10 hours after dissolution, and centrifuging, washing, and drying the obtained product to obtain the porous calcium carbonate.

2. The environmentally friendly flame-retardant rubber-plastic composite shed blanket according to claim 1, characterized in that: The intermediate insulation layer comprises the following components in parts by weight: 15-20 parts of nitrile rubber, 3-5 parts of polyvinyl chloride resin, 4-7 parts of foaming agent, 3-5 parts of ethylene-vinyl acetate copolymer, 20-30 parts of talc, 13-15 parts of chlorinated paraffin oil, 1-2 parts of epoxy soybean oil, 2-4 parts of protective wax, 3-5 parts of carbon black, 0.2-0.3 parts of active agent, 0.1-0.3 parts of stearic acid, 10-20 parts of flame retardant, 0.1-0.3 parts of antioxidant, 1-3 parts of accelerator and 0.1-0.3 parts of vulcanizing agent.

3. The environmentally friendly flame-retardant rubber-plastic composite shed blanket according to claim 1 is characterized in that: The fireproof silicone fiber veneer layer is a glass fiber cloth layer coated with fluorosilicone rubber, and the mass ratio of the fluorosilicone rubber to the glass fiber cloth is (10-15): (85-90).

4. The environmentally friendly flame-retardant rubber-plastic composite shed blanket according to claim 1 is characterized in that: The thickness of the polytetrafluoroethylene anti-aging layer is 0.2 mm, the thickness of the intermediate thermal insulation layer is 1-5 cm, and the thickness of the fireproof silicone fiber veneer layer is 0.2 mm.

5. The environmentally friendly flame-retardant rubber-plastic composite shed blanket according to claim 1 is characterized in that: The molar ratio of the calcium chloride to the sodium carbonate is 1:

1.

6. The environmentally friendly flame-retardant rubber-plastic composite shed blanket according to claim 1, characterized in that: The preparation method of the polytetrafluoroethylene anti-aging layer comprises the following steps: polytetrafluoroethylene is mixed with anionic fluorocarbon surfactant, triisostearyl isopropyl titanate and porous calcium carbonate, and then melt-extruded to obtain the polytetrafluoroethylene anti-aging layer.

Citation Information

Patent Citations

  • Foam insulation quilt

    CN104663315A

  • Nano calcium carbonate modified polytetrafluoroethylene composite material for sealing valve

    CN104592694A

  • Agricultural composite film

    CN105850588A

  • Short-chain-free chlorinated paraffin rubber and plastic product and preparation method thereof

    CN111117017A

  • Big -arch shelter heat preservation quilt and big -arch shelter

    CN206835764U